Adaptasi Psikologis Pasien Yang Menjalani Hemodialisis - Laily Isroin (Universitas Pesantren Tinggi Darul Ulum, 2017)
Abstract The problems faced by GGK patients are complex in addition to physical problems, as well as psychological and economic problems posed to serious threats to CKG patients. It takes a tremendous psychological adaptation of patients and families to deal with congenital problems. This study was conducted to analyze the ability of psychological adaptation of GGK patients undergoing hemodialysis therapy. This research was conducted in Kabupaten Ponorogo, with the sample number of 100 respondents taken by purposive in RSUD Dr. Hardjono Ponorogo . Crosssectional analytic design is done to measure the ability of psychological adaptation which includes self concept, interdepensi, and role function. To analyze the relationship between variables bivariate analysis was used with chi square test. The psychological adaptability of hemodialysis patients is 74% adaptive, 69% adaptive and 87% adaptive. Age is related to the adaptation ability of patients who undergo hemodialsis on the role and self-concept. Respondents aged less than 50 years have the potential to experience self-concept adaptation failure of 0.3 times (OR = 0.27; CI = 0.104-0704) and the role of 0.4 times (OR = 0.406; CI = 0.170-0.969) of respondents Who are over 50 years old. There is a relationship between the work with the ability of respondents to adaptation of selfconcept and role. Respondents who were not working at risk 4 times experienced adaptation failures in self-concept aspects (OR = 3,824; CI = 1,315-11,115) and roles (OR = 3,631; CI = 1,266-10,414) compared with respondents working Keywords: Psychological Adaptation, Hemodialysis